STRATEGI GURU AL-QUR'AN HADIS DALAM MENINGKATKAN KEMAMPUAN BACA AL-QUR'AN SISWA KELAS X DI MA NWDI PRINGGASELA - Baiq Erna Januarti; H.Abdul Hayyi Akrom; Ruwaida Ruwaida (Hijri, 2025)
This study aims to reveal the strategies used by Al-Qur'an Hadith teachers in improving the Qur'an reading ability of tenth-grade students at MA NWDI Pringgasela. The ability to read the Qur'an is a fundamental aspect of Islamic education, as it serves as the foundation for students to correctly understand the content and message of the Qur'an. Al-Qur'an Hadith teachers play a crucial role in shaping this ability through a structured and systematic learning process. This research employs a qualitative descriptive approach using field research, focusing on the objective depiction of real conditions in the field. Data collection techniques include observation, interviews, and documentation to obtain in-depth insights into the teaching strategies applied by the teachers. The results of the study show that the main strategy used by Al-Qur'an Hadith teachers at MA NWDI Pringgasela is the expository strategy, which emphasizes direct delivery of material from teacher to students. This strategy is implemented through two main methods: the lecture method and the talaqqi method. Through lectures, teachers explain the rules of tajwid, makharijul huruf (points of articulation), and the ethics of reading the Qur'an. Meanwhile, the talaqqi method is used to train students' reading skills by listening to and imitating the teacher's recitation to correct pronunciation errors. The application of these methods has proven effective in improving students' ability to read the Qur'an accurately while fostering discipline and love for the Qur'an.